Gut Microbiota and Cardiovascular Disease. Issue 4 (31st July 2020) - Witkowski, Marco; Weeks, Taylor L.; Hazen, Stanley L.
Abstract : Fecal microbial community changes are associated with numerous disease states, including cardiovascular disease (CVD). However, such data are merely associative. A causal contribution for gut microbiota in CVD has been further supported by a multitude of more direct experimental evidence. Indeed, gut microbiota transplantation studies, specific gut microbiota–dependent pathways, and downstream metabolites have all been shown to influence host metabolism and CVD, sometimes through specific identified host receptors. Multiple metaorganismal pathways (involving both microbe and host) both impact CVD in animal models and show striking clinical associations in human studies. For example, trimethylamine N-oxide and, more recently, phenylacetylglutamine are gut microbiota–dependent metabolites whose blood levels are associated with incident CVD risks in large-scale clinical studies. Importantly, a causal link to CVD for these and other specific gut microbial metabolites/pathways has been shown through numerous mechanistic animal model studies. Phenylacetylglutamine, for example, was recently shown to promote adverse cardiovascular phenotypes in the host via interaction with multiple ARs (adrenergic receptors)—a class of key receptors that regulate cardiovascular homeostasis. In this review, we summarize recent advances of microbiome research in CVD and related cardiometabolic phenotypes that have helped to move the field forward from associative to causative results. We focus on microbiota and metaorganismal compounds/pathways, with specific attention paid to short-chain fatty acids, secondary bile acids, trimethylamine N-oxide, and phenylacetylglutamine. We also discuss novel therapeutic strategies for directly targeting the gut microbiome to improve cardiovascular outcomes.